Pemanfaatan Limbah Cangkang Kerang Menjadi Cinderamata - Syahmidarni Al Islamiyah; Rosdiani Azis; Adnan Engelen (Jurnal Ilmiah Pangabdhi, 2021)
One of the organic wastes that can be used for handicraft goods is Seashell. One of the artisanal items is a souvenir. The use of this waste is a type of community-owned skill. By using shell waste that has added value, this community service aims to make souvenirs. The methods in this activity include material presentation, discussion and training. The results obtained in this community service activity include  1) a lot of shell waste in Tanjung Kramat Village, Hulonthalangi District, Gorontalo District, Gorontalo Province, which can be made into souvenirs as souvenirs from the area; 2) participants in community service have the skills and experience to make shell souvenirs. The conclusion of this activity is to learn information and skills to use shellfish waste as souvenirs for individuals who engage in this service. The proposal for this operation to be carried out on an ongoing basis is to pursue special government assistance to grow it into a community-based economic activity and to promote Tanjung Kramat tourism.